[PP.14.18] USEFULNESS AND FEASIBILITY OF CONCOMITANT ABPM AND ECG MONITORING OF HYPERTENSIVE PATIENTS IN DETECTING SILENT ATRIAL FIBRILLATION. (September 2016) - Varga, A.; Gal, C.M.; Negovan, A.E.; Magdas, A.; Puiac, C.I.; Tilea, I.
Abstract : Objective: Diagnostic of silent atrial fibrillation (AF) in order to prevent stroke in hypertensive patients could hold off further sequels. A single device performing simultaneous recording of ambulatory blood pressure monitoring (ABPM) and continuous electrocardiographic (ECG) monitoring in hypertensive patients could extend the diagnostic possibilities for screening of asymptomatic AF. Design and method: A single-center prospective screening study using the Custo Holter ABDM custo screen 400 device (custo med GmbH, Germany) performing simultaneous ABPM and ECG monitoring for 48 hours, was used in outpatient cardiology clinic on consecutive hypertensive patients, during one year (December 2014 to December 2015). Hypertensive patients with previous documented history of AF, palpitations or syncope, implantable pacemakers or defibrillators were included. In order to assess left ventricular hypertrophy (LVH) and systolic function (ejection fraction EF) a transthoracic echocardiography was performed in every case using an Esaote MyLab ™50XVision ultrasound machine. Results: 125 subjects (67 male, age 64 ± 7.0 years; ejection fraction 56% ± 9%) were enrolled. Paroxysmal episodes of AF were detected in 13 subjects (10.4%). Out of 13 hypertensive patients, 10 cases (83.3%, p < 0.05) required continuous oral anticoagulation (NOAC or VKA), according to CHA2DS2-VASc SCORE for AF. Ventricular ectopic beats in couplets (2 to maximum 5 beats) were detected in 3 (2.4%) patients. There was no statistical correlation between LVH, ejection fraction and presence of AF. Conclusions: Adequately strategies to improve AF detection and prevention of further sequels are feasible in outpatients using extended ECG screening for asymptomatic AF. If confirmed in extended studies, screening for AF in hypertensive patients could have a significant impact on long-term management of these patients.